2018
DOI: 10.1186/s12864-018-4626-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mitochondrial genomics of cryptophyte algae: gene shuffling and dynamic mobile genetic elements

Abstract: BackgroundCryptophytes are an ecologically important group of algae comprised of phototrophic, heterotrophic and osmotrophic species. This lineage is of great interest to evolutionary biologists because their plastids are of red algal secondary endosymbiotic origin. Cryptophytes have a clear phylogenetic affinity to heterotrophic eukaryotes and possess four genomes: host-derived nuclear and mitochondrial genomes, and plastid and nucleomorph genomes of endosymbiotic origin.ResultsTo gain insight into cryptophyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 80 publications
2
24
1
Order By: Relevance
“…The mitogenomes of Haptophyta 133 , Centrohelida 134 , and Cryptophyta 135 have been sequenced. (Sometimes these lineages have been grouped together within Hacrobia, although the monophyly of this group is highly controversial 136 .)…”
Section: Other Eukaryote Mitogenome Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The mitogenomes of Haptophyta 133 , Centrohelida 134 , and Cryptophyta 135 have been sequenced. (Sometimes these lineages have been grouped together within Hacrobia, although the monophyly of this group is highly controversial 136 .)…”
Section: Other Eukaryote Mitogenome Structuresmentioning
confidence: 99%
“…There are up to 12 unassigned ORFs. The mitogenomes of Cryptophyta are circular molecules ranging in size from 37 to 54 Kb 135 (Figure 2). The mitogenomes contain the same set of OXPHOS system protein-coding genes reported in Marophrys sp.…”
Section: Other Eukaryote Mitogenome Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, no high-quality nuclear genome sequence is available for any cryptists except a cryptophyte Guillardia theta (Curtis et al, 2012) and a goniomonad Goniomonas avonlea (Cenci et al, 2018). Likewise, the complete mtDNAs are available from nine members of Cryptista, albeit seven out of the nine are cryptophytes (Hauth et al, 2005;Kim et al, 2008;Kim et al, 2018). Besides cryptophyte mtDNAs, Nishimura et al (2016) and Cenci et al (2018) reported the complete mtDNAs of P. bilix and G. avonlea, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Cryptophytes have strong adaptability to light and temperature and they become the dominant species in both winter and summer. Phototrophs of cryptophytes contain plastids with chlorophyll-a and -c, as well as phycobilins, as accessary pigments (Kim et al 2018). There are four genomes in cryptophyte cells: host-derived nuclear and mitochondrial genomes, and plastid and nucleomorph genomes of endosymbiotic origin (Douglas et al 1991).…”
mentioning
confidence: 99%